Resistance Level of Crocidolomia pavonana Against Profenofos Synthetic Insecticide and its Susceptibility To Azadirachta Indica Seed Extract - Danar Dono; Yogas Dwi Pratiwi; Safri Ishmayana; Djoko Prijono (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2018)
This research was conducted to know resistance level of Crocidolomia pavonana to a profenofos synthetic insecticide and to know susceptibility of C. pavonana to Azadirachta indica seed extract. The experiment using two bioassay methods, dry film method and feeding method. Field population of C. pavonana obtained from 3 villages in Lembang district i.e.Cibogo, Cikole and Kayu Ambon village. The standard insect has been maintenance more than 20 generations in the laboratory as a comparison. The result of the experiment indicated that population of C. pavonana form Cikole, Cibogo and Kayu Ambon village were resistant to profenofos insecticide with resistance ratio (RR) was low (1< RR ≤ 5). Resistance Ratio of C. pavonana from the third village were 4.69 and 4.83; 1.02 and 1.1 and 1.16 and 1.9 respectively (dry film and feeding method). The value of the resistance ratio was greater through the feeding assay compared to the contact assay. This indicated that the mechanism of C. pavonana resistance was likely to occur mainly in the digestive tract of insects. Enzime activity of the different sample population of C. pavonana indicated variation in their activity. This was indicated that every sample from different field could develop different mechanism of resistance. The toxicity study of A. indica seed extract to C. pavonana indicate that the field population of C. pavonana from the third village was susceptible to seed extract of A.indica with value RR of less than one point. Therefore seed extract of A. indica could be used as alternative control against C. pavonana which resistant to profenofos synthetic insecticide.Keywords: Resistance mechanism, Resistance ratio, Synthetic insecticide, Botanical insecticide